Civil society as a fundamental partner in environmental governance - Hafsi, Mellah (The International tax journal, 2025)
In light of the state’s declining role and its inability to meet individual needs or to effectively manage social domains that have undergone a profound transformation from mediation and reconciliation to structured institutional partnership and cooperation, civil society has emerged as a new actor uniquely capable of filling these gaps. Having long confined its engagement to addressing issues of acute contention between the state and citizens, particularly in matters related to rights and social concerns, civil society organisations have transcended their traditional role as a complementary sector to the state. They now stand as indispensable social partners in both the formulation and implementation of public policies, operating with autonomy from other active stakeholders.